The role of free zones in Maghreb economic integration - Hamid Chachoua (Dirassat Journal Economic Issue, 2016)
The Contribution of Free zones in economies growth of many countries which adopted as a strategy by gradual change from oriented economy to a free economy where there are more than 1735 free zone distributed across 133 countries. According to statistics in 2008. Due good investment climate that provided by these circumstances worked free zones to attract foreign direct investment and encourage local investors, this is what led to the activation of the production process and increase the global competitiveness of it and contribute to the increase in exports. Several border countries established joint free zones to activate the economic dynamism among them as the initial phase of regional economic and regional integration due friction economics of these circumstances countries among themselves and from the attempt to approximate future visions and joint strategies and work later to form a regional economic bloc. In this article we will highlight the economic benefit from the establishment of areas free border and how to activate the Maghreb economic integration.